Molecular markers associated with drug resistance in PFMDR-1 gene of Plasmodium falciparum in Gombe Local Government Area, Gombe State, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2026)
Malaria is a serious deadly disease in Nigeria, and for long prevention and treatment of the disease depended heavenly on different classes of synthetic drugs. However, Plasmodium falciparum has developed resistance to almost all the classes of the synthetic antimalarial drug in use, including the most recently recommended drugs (artemisinin-based combination therapies). The aim of this research was to identify and characterize molecular markers associated with drug resistance in pfmdr-1 genes of P. falciparum from Gombe Local Government Area (LGA). Two hundred study subjects were recruited for the research from 3 selected hospitals. Blood samples were collected using vein puncture technique and analyzed using Giemsa stain, rapid diagnostic test, and polymerase chain reaction. Zymo DNA extraction kit was used to extract the DNA samples, from which 167 samples confirmed to be positive by microscopy. A NanoDrop spectrophotometer was used to determine the concentration and purity of the extracted DNA. Fifty seven true-positive samples with high DNA concentration and purity were selected and used for the molecular analysis. Nested polymerase chain reaction was used to amplify the portion of the selected genes and the amplicons were sequenced for the actual determination of single nucleotide polymorphism in pfmdr-1 gene. Single point mutation was observed in four of the variants (N86Y, Y184F, N1042D, and D1246Y) and the highest prevalence (34, 59.64%) was from the Y184F variant. Conclusively, some basic biomolecular makers of pfmdr-1 gene were reported from Gombe LGA. Further research should be carried out in the local government area using a large sample size and targeting some other candidate bio markers of the gene.